2021
DOI: 10.1016/j.nicl.2021.102844
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically reduced neural flexibility recovers during psychotherapy of OCD patients

Abstract: Highlights Psychiatric impairment is associated with decreased neural flexibility. Psychotherapy was able to increase the neural flexibility of the patients. Psychotherapy should increase adaptivity of cognitive-emotional-behavioral patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…As to the specific functional connection between in-depth interviews and urinary neopterin complexity found in this re-evaluation, we assume that the decreasing neopterin complexity days before and during interviews was related to stress that rendered the psycho-immunological system less flexible and, thus, less adaptable. Thereafter, however, the subject was relieved, ultimately leading to a restoration of the flexibility/adaptability of the emotional and immune systems (see in Figure 3 the slight increase in neopterin complexity after interviews) ( 49 ). In line with this interpretation, neopterin complexity was positively correlated with DC scores in irritation, anxiousness/depressiveness, and mental activity.…”
Section: Discussionmentioning
confidence: 99%
“…As to the specific functional connection between in-depth interviews and urinary neopterin complexity found in this re-evaluation, we assume that the decreasing neopterin complexity days before and during interviews was related to stress that rendered the psycho-immunological system less flexible and, thus, less adaptable. Thereafter, however, the subject was relieved, ultimately leading to a restoration of the flexibility/adaptability of the emotional and immune systems (see in Figure 3 the slight increase in neopterin complexity after interviews) ( 49 ). In line with this interpretation, neopterin complexity was positively correlated with DC scores in irritation, anxiousness/depressiveness, and mental activity.…”
Section: Discussionmentioning
confidence: 99%
“…One additional topic that was not included in the nine criteria for integration we presented is the integration of psychological and brain‐directed interventions. It may prove worthwhile for the field to invest more towards the combination of noninvasive methods of neuromodulation or neurostimulation and psychotherapy (e.g., de Charms et al, 2005; Fox et al, 2014; Tass & Popovych, 2012), particularly inasmuch as psychological treatments have the capacity to reorganise neuronal network dynamics (Schiepek et al, 2021). It should be noted again that complexity science allows for the investigation and modelling of brain network dynamics and psychotherapy process using a common framework.…”
Section: Discussionmentioning
confidence: 99%
“…This theoretical perspective has been supported by several studies of psychotherapy processes as well. For example, dynamical indicators of transitions have been observed in clients' daily ratings of experience during psychotherapy, which include discontinuous transitions and critical instabilities that serve as precursors to these order transitions (Haken & Schiepek, 2010; Hayes et al, 2007; Olthof et al, 2019; Schiepek, Heinzel, et al, 2016; Schiepek, Stoeger‐Schmidinger, et al, 2016), chaos (i.e., sensitive dependency of the dynamics on initial conditions, dynamic noise and parameter values, which implies limited predictability; Schiepek et al, 2017) and shifting synchronisation patterns among cognitive‐emotional and neuronal activity (Schiepek et al, 2013; Schiepek et al, 2021). Similarly, studies have shown dynamic synchronisation of the client–therapist interactions (Kleinbub, 2017; Kowalik et al, 1997; Ramseyer & Tschacher, 2008; Strunk & Schiepek, 2006), stability conditions as necessary conditions for change, and the appearance of order transitions before or independent of the timing of interventions (Heinzel et al, 2014).…”
Section: Genuine Integrationmentioning
confidence: 99%
“…low vs. rapid cycling of emotions in bipolar disorders, intensity of emotional fluctuations in Borderline Personality Disorder, switching between ego-states which are enslaving different emotions and cognitions in dissociative identity disorders vs. dissolving pathological over-synchronization [3], to be stuck in reduced ways of mental functioning (e.g. craving, numbness) vs. flexibility and adaptivity [68]. If mental disorders can be seen as "dynamic diseases" [69,70] then we should open our judgment on therapeutic effects on changing dynamics.…”
Section: Diversity Of Pattern Transitionsmentioning
confidence: 99%